Self-Management and Learning Discipline: A Correlational Study of Vocational High School Students - Yahya, Dahlia Nur; Masrukhin, Akhmad Rudi (Universitas Muhammadiyah Metro, 2026)
Self-management and learning discipline are critical competencies that influenceacademic success, particularly in vocational education where practical andtheoretical learning demands high student autonomy. This study investigates therelationship between self-management and learning discipline among vocational highschool students. A quantitative correlational design was employed, with datacollected from 48 tenth-grade students using validated Likert-scale questionnaires.Descriptive statistical analysis indicated that students exhibited moderate to highlevels of both self-management and learning discipline. Pearson product-momentcorrelation analysis revealed a statistically significant positive relationship betweenthe two variables (r = 0.66, p < .001), indicating that students with stronger selfmanagement skills tend to demonstrate higher learning discipline. These findings underscore the importance of integrating self-management development into vocational curricula to foster disciplined learning behaviors. Educators and school administrators are encouraged to implement structured interventions that enhance students’ time management, goal setting, and self-regulation. This study provides empirical evidence supporting the role of self-management as a foundational driver of academic discipline in vocational education contexts.